2017
DOI: 10.1097/pr9.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

Regular physical activity prevents development of chronic muscle pain through modulation of supraspinal opioid and serotonergic mechanisms

Abstract: The current study shows that blockade of opioid receptors systemically in the periaqueductal gray and the rostral ventromedial medulla prevents analgesia by 8 weeks of wheel running in a chronic muscle pain model. We further show increases in serotonin transporter expression and reversal of hyperalgesia with a selective reuptake inhibitor in the rostral ventromedial medulla in the chronic muscle pain model, and exercise normalizes serotonin transporter expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 107 publications
2
68
2
3
Order By: Relevance
“…The current study showed that physically active animals have less dermorphin-488positive neurons, but not TPH-positive neurons, projecting to the spinal cord when compared to sedentary animals in the RVM, but not the NRO/NRP. These data are consistent with prior studies showing regular exercise produces analgesia through endogenous opioid systems in the RVM and spinal cord [6,39,60]. Since mu-opioid receptors are purported to be ON-cells and facilitate nociception [17,24], these data suggest that there is less descending facilitation from the RVM in physically active mice.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The current study showed that physically active animals have less dermorphin-488positive neurons, but not TPH-positive neurons, projecting to the spinal cord when compared to sedentary animals in the RVM, but not the NRO/NRP. These data are consistent with prior studies showing regular exercise produces analgesia through endogenous opioid systems in the RVM and spinal cord [6,39,60]. Since mu-opioid receptors are purported to be ON-cells and facilitate nociception [17,24], these data suggest that there is less descending facilitation from the RVM in physically active mice.…”
Section: Discussionsupporting
confidence: 91%
“…Since RVM and the NRO/NRP are key serotonergic nuclei, and increased serotonin in the RVM can reduce pain [6,39,51], we examined if there were differences in TPH immunoreactivity in dermorphin-488-positive cells. Figure 4 Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations